Soil Displacement Using Disc Plough in a Clayey Loam Soil - Dazugo, E. (University of Ghana, 2016)
Soil displacement by tillage is a major contributor to the redistribution of soil particles within the soil profile. The extent of soil redistribution eventually has an effect on the performance of crop production. It is, therefore, valuable to investigate soil displacement by disc plough since it is known to be the widely used primary tillage implement in Ghana. Consequently, a study was conducted at the Livestock and Poultry Research Centre of the University of Ghana (LIPREC) with a tractor - disc plough aggregate. Using three ploughing speeds (5km/hr, 7km/hr and 9km/hr) and three ploughing depths (12cm, 15cm and 18cm), a 32 factorial experiment was designed for this study. The essential soil and tracer characteristics were verified. The movement of tracers inserted into the soil measure soil displacement in the x-y-z coordinate directions. The data was statistically analysed to establish the effects of ploughing speed and depth on soil displacement. Results from our experimental study showed that on the average the disc plough tillage moved soil particles through a distance of 59.8 ± 12.5cm. Ploughing speed and depth had significant effects (p ≤0.05) on soil displacement by the disc plough. Increasing ploughing speed generally led to increase in soil displacement with a wider mix. The study also showed that most of the tracers were spread within the region of 12cm above to 6cm below the original surface of the field. The disc plough mixes majority of the transported soil particles within this region of the tilled layer. At higher speed of 9km/hr the displaced soil particles were highly mixed within this region whiles at 5km/hr the displaced soil particles were concentrated within the upper 6cm.
Thesis(Mphil)-University of Ghana, 2016
Keywords: Soil Displacement; Disc Plough; Clayey Loam Soil